(untitled) (Bangladesh Journal of Botany, 2025)
Improved nitrogen fertilizer management in organic rice cultivation improves nitrogen use efficiency, lowering N losses and, ultimately reducing environmental deterioration. A field experiment was conducted to assess the impact of twice-split organic nutrient management strategy on N absorption and nitrogen use efficiencies (NUE) in direct seeded rice production (DSR) system. The N absorption pattern estimated through logistic model showed that the fast N uptake time with VC100 was considerably longer than that of CF100. Synchronization of soil available N and crop N demand for a longer duration during the fast N uptake phase, vermi compost (VC) applied in twice-splits increased N uptake, dry matter production, yield characteristics and grain yield compared to CF100. It was concluded that VC applied in twice, i.e., basal fertilizer and top dressing at 5 days before panicle initiation was as effective as CF100 in enhancing NUE of DSR in lateritic soil. Bangladesh J. Bot. 54(2): 311-318, 2025 (June)